Sleep duration and personality in Croatian twins - Bratko, Denis; Vukasović, Tena; Butković, Ana (2014)
The objective of this study was to examine which genetic and environmental influences contribute to individual differences in sleep duration in a sample of Croatian adolescent/early adult twins, as well as to investigate the relationship between personality and sleep duration. Participants included 339 twin pairs (105 MZ and 234 DZ) aged between 15 and 22 years. They reported on their average sleep duration and personality. Broad heritability estimate (additive and non-additive genetic influences) for sleep duration was .63, while for personality estimates ranged between .47 and .62. Significant negative phenotypic associations with neuroticism and openness were mainly genetically mediated, 100% and 80% respectively. Only 6% of the sleep duration variance was explained by genetic influences shared with neuroticism and openness. In regression analysis age, gender and five personality traits explained 5% of sleep duration variance with neuroticism and openness as significant predictors. Comparison of short, moderate and long sleepers showed that participants in short sleepers group had significantly higher neuroticism scores than groups of moderate and long sleepers, as well as significantly higher openness score than group of long sleepers. All this indicates that personality traits of neuroticism and openness contribute to the prediction of sleep duration due to overlapping genetic influences that contribute both to these personality traits and sleep duration. However, since phenotypic overlap of personality and sleep duration is relatively week, heritability of sleep duration is not only related to individual differences in personality traits, so future research needs to examine other phenotypic correlates of sleep duration.
Projekt MZOS